Design Interface & Implementation For In-Vehicle Personal Computing - Muhammad Helmi bin Abdul Ali, Muhammad Helmi (Universiti Teknologi Petronas, 2009)
Current technology permits small size computer with huge amount of hard disk space as well as sufficient performance and therefore makes it easier for one to design such a system. The embedded device placed inside a vehicle is expected to have functions such as allowing vehicle passengers to enjoy accessing their favourite videos and music and up to a point where it can also become an assistant for drivers using navigation system function. The aim of this project is to demonstrate that as a proof of concept of In-Vehicle Infotainment (IVI) is feasible.